Feeling of the selected climacteric symptoms depending on the climacteric phase and type of menopause - Stachoń, Aleksandra Jadwiga (Menopause Review/Przegląd Menopauzalny, 2013)
Background : Hormonal changes in women during the climacteric period, which result from the reduced ovarian function, manifest in various physical and psychological symptoms. The intensity of these signs mostly depends on biological and social factors, however, the sensation of menopausal symptoms varies from person to person and from population to population. It mostly depends on the present level of sex hormones, general biological conditions and women’s health. The aim of the cross-sectional study was to determine the course of climacterium in the aspect of frequency of menopausal symptoms in different groups of women. Material and methods : A questionnaire study was conducted in the health care centers during prophylactic medical examinations. Near 900 women aged 40 and over from the south region of Poland were questioned in 2005-2007. Climacteric symptoms were analyzed in groups of women divided depending on the climacterium phase and type of menopause. Both the questionnaire and the study were accepted by the Bioethical Committee of the Jagiellonian University. The following symptoms were analyzed: hectic fever, night sweat, insomnia, restlessness and tantrum, palpitation and chest distress, dizziness and headache, irregular menstruation and dry vagina. Results and conclusions : The frequency of selected menopausal symptoms differs in the successive phases of climacterium as well as in the group of a different type of menopause. Most of climacteric signs appeared more frequently after menopause, especially in women using hormonal supplementation. Presumably, the high intensity of symptoms impelled these women to use hormonal treatment.